RELASI “AKU” DENGAN “YANG LAIN” MENURUT PERSPEKTIF EMANUEL LEVINAS (Sebuah tinjauan Filsafat Sosial) - Herman Yosep Utang (Jurnal Pluralis, 2023)
The presence of humans in the universe has an existential meaning implies a relation of the self to the Other in a unity and wholeness (totality). In the perspective of Emanuel Levinas, the tie-in between I and the Other is the appearance of the self and the existential reality behind it. The countenance shows the process of the link between I to the Other which existentially invites each of me to be ethically responsible for being the guardian of others by letting others be themselves. The other (alterity) must not be reduced and alienated from himself and only carry out certain anonymous, pragmatic and instantaneous functions.